(untitled) (Bangladesh Journal of Public Administration, 2022)
Virtual meetings made official meetings possible during the COVID-19 pandemic, contributed to the reduction of fossil fuel consumption, and saved time, cost, and travel time for officials. Considering the benefits, it is essential in the present context to study if the continuation of virtual meetings in the post-COVID period is required or not. This research tries to explore how effective virtual meetings were during the pandemic period of COVID-19 in government offices in Bangladesh and if their continuation in the future is feasible or not. This study investigates the difficulties in hosting and organizing virtual meetings that various district and Upazila-level government offices in Bangladesh face. The views of government officials posted in 24 districts about the prospects of virtual meetings and challenges are analyzed in this study. Acknowledging the prospects and challenges, it is suggested that the continuation of virtual and, in some cases, hybrid meetings are required in government offices to assure sustainable development and obtain success in the Fourth Industrial Revolution.